Recent Advances in Dual Disorders (Addiction and Other Mental Disorders) - Torrens, Marta; Adan, Ana (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Dual disorders, meaning the coexistence in the same individual of a substance use disorder and another mental disorder, have become an area of great interest in the fields of psychiatry and addiction and in health overall due to their high prevalence, clinical relevance and multicultural presence. This book includes a compilation of papers published between the end of 2021 and the beginning of 2023 focused on recent advances in dual disorders. The contributions present a broad look at various relevant aspects. Among them are the characterization of patients treated in different services, with special interest in the risk of overdoses, suicidal attempts and HIV, as well as the so-forgotten gender perspective and the impact of the COVID-19 pandemic on the attention of addiction centers. One of the first studies to consider the comorbidity of gambling disorders with substance use is also presented. The possible usefulness of explanatory models of machine learning for diagnosis and for performing chronobiological measurements that allow a more individualized treatment stand out among the novel contributions to the field of dual disorders. The aim of each of the contributions of this reprint is to be transferred for the benefit of clinical practice.